Multidimensional evaluation of the quality of socio-spatial environments in inner-city transitional edges: a case study of Chongqing’s Yuzhong district - He, Xiao; Kozlowski, Marek; Ujang, Norsidah; Ma, Yue (Multidisciplinary Digital Publishing Institute, 2024)
In rapid urbanization, the socio-spatial environment between inner-city functional areas faces numerous challenges. Assessing and enhancing the environmental quality of these areas has become an urgent research issue. This study quantitatively evaluates the social-spatial environment of inner-city transitional edges, selecting Chongqing’s Yuzhong District as the case study area. It explores the relationship between spatial environmental factors and social activities. Integrating spatial data, internet “big” data, and field survey data, a multidimensional evaluation of the quality of the social-spatial environment framework is constructed, encompassing four dimensions: connectivity, social function, comfort, and conviviality. Subsequently, a multiple linear regression model is used to explore the main environmental factors influencing social activities on transitional edges. The results show that the density of street trees, lighting facilities, functional density, and functional diversity significantly impact social activities, demonstrating the correlation between the spatial environment of inner-city transitional edges and social activities. Corresponding optimization strategies for each dimension in transitional edges are then summarized. This study provides references for coordinating inner-city functional areas, optimizing urban environments, and promoting sustainability. It can also be applied to a broader range of transitional edge evaluation studies.